DESENVOLVIMENTO, CARACTERIZAÇÃO E AVALIAÇÃO DA ATIVIDADE ANTIMICROBIANA E ANTIBIOFILME DE NANOCÁPSULAS DE DIHIDROMIRICETINA EM CATETERES URINÁRIOS - Dalcin, Ana Júlia Figueiró (2015)
Nosocomial infections associated with biofilm formation in urinary catheters are among the leading causes of complications due to high antimicrobial resistance. An alternative is Dihydromyricetin (DHM), a flavonoid compound extracted mainly from grossedentata Ampelopsis plant, a vine of southern China, where you been widely used as a kind of healthy tea by the population. DHM has demonstrated different pharmacological properties. Among them stands out strong antimicrobial activity to various microorganisms.Therefore, the DHM has low lipid solubility consequently low biodisponibility. The nanoencapsulation can contribute to the improvement of the characteristics of drugs, as increased apparent solubility, protection against toxicity, increased drug activity and stability, sustained release and protection from degradation have been reported. The aim of this study was to evaluate the feasibility of DHM encapsulation and evaluate the influence on antimicrobial and antibiofilm activities in front of urinary catheters with Pseudomonas aeruginosa strains. The analytical method was devoloped and validated to indicate the stability of DHM and to determinaton it in polymeric nanocapsules by high-performance liquid chromatography. The developed method proved to be linear, specific, precise, accurate and robust for determining of DHM in polymeric nanocapsules. The results of the stability indicative studies demonstrated greater stability of nanocapsules than compared with free DHM, suggesting a protective the degradation of the nanostructure. The physicochemical characterization and the stability study of formulations demonstrated to be appropriate with nanometer diameter, positive zeta potential, the quantification of DHM close to the theoretical content, spherical morphology and uniform distribution of particles. The best conditions for storage of the suspensions without losing its physical and chemical characteristics during the period of 90 days was under refrigeration. The results showed that antimicrobial activity of the compound in the free form eliminate the microbial population in 12 hours while the nanocapsules containing DHM took 24 hours to remove the microbial population, extending up to 96 hours in a sustained manner. The antibiofilm activity of the formulations resulted in the eradication of biofilms both in free DHM formulations as in nanocapsules of DHM during the analyzed periods. However, within 96 hours the results of the inhibition of biofilm by DHM nanocapsules were more effective compared with free DHM, 67% of eradicating biofilm population. Thus, the formulation of nanocapsules DHM may be employed in the eradication of biofilms urinary catheters, it may be used as an innovative strategy.